2006
DOI: 10.1111/j.1365-2133.1994.tb08492.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous photosensitivity in dermatomyositis

Abstract: Summary The incidence and nature of cutaneous photosensitivity were studied in 10 patients suffering from dermatomyositis. Five reported an abnormality, which consisted of photoaggravation of preexisting cutaneous lesions in three, and abnormal transient erythemal responses in two. Monochromatic irradiation testing of all 10 patients demonstrated reduced minimal erythemal doses in two, at 307.5nm, and at 340 and 360nm, respectively; only the latter individual had clinical light sensitivity. Exposure to low‐dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 9 publications
1
21
0
2
Order By: Relevance
“…Intriguingly, whereas previous clinical predictors of malignancy were not confirmed, photosensitivity ( P = 0·03) and periungual erythema ( P = 0·02) were associated with absence of malignancy in our cohort. Although DM is classically associated with photosensitivity, several studies showed that only about 50% of patients are truly photosensitive . This is similar to our observation, where about one‐third of our patients were photosensitive (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, whereas previous clinical predictors of malignancy were not confirmed, photosensitivity ( P = 0·03) and periungual erythema ( P = 0·02) were associated with absence of malignancy in our cohort. Although DM is classically associated with photosensitivity, several studies showed that only about 50% of patients are truly photosensitive . This is similar to our observation, where about one‐third of our patients were photosensitive (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of increased cutaneous photosensitivity in DM patients, however, is relatively poorly documented, the nature of the photosensitivity in the disorder has not been established and photosensitivity is tested in only a few cases (5, 8). Therefore, we decided to investigate carefully the cutaneous photosensitivity of every newly diagnosed DM hospitalized in our clinic since 1999, to expand our knowledge and to compare the results with those in patients with lupus erythematosus (LE) and healthy controls.…”
mentioning
confidence: 99%
“…Despite these results, the largest open trial to date of rituximab for DM demonstrated modest improvement of muscle disease but limited effects on cutaneous disease [18]. In this trial of eight patients, three patients achieved partial remission at week 24, defined by a reduction in muscle deficit of at least 50%.…”
Section: Rituximabmentioning
confidence: 96%
“…One study did find that DM patients, similar to those with lupus erythematosus, showed a significantly reduced minimal erythema dose to UVB irradiation compared with healthy individuals [17]. In a study by Cheong et al, lesions of DM with solar-simulated radiation were only able to be reproduced in one out of six patients; however, five out of ten patients indicated that light would exacerbate their existing cutaneous lesions [18].…”
Section: Photoprotectionmentioning
confidence: 99%